Pengaruh Pemasaran Digital dan Kualitas Produk Terhadap Kepuasan Konsumen Perempuan di Kota Metro - Megasari Megasari; Dafa Rafif Pratama (Global Leadership Organizational Research in Management, 2024)
This research aims to determine the influence of digital marketing and product quality on consumer satisfaction in culinary businesses in Metro City, Lampung Province. The type of research used is explanatory research with a quantitative approach. The population in this research is consumers who have visited and carry out culinary product purchase transactions. The sample used in this research was 100 female respondents taken using purposive sampling, Meanwhile, the data collection procedure was carried out using field studies include interviews, questionnaires, observation and documentation. The research results obtained were analyzed with statistical tools using the smartPLS program, shows that digital marketing and product quality have a positive effect on consumer satisfaction.